The evaluation of the solar activity influence on aviation accidents occurrence in 1944 – 2009 years - Поліщук, С.Т. (Proceedings of National Aviation University (archive), 2010)
On the basis of statistical analysis the weak correlation between the number of aviation accidents and the indexof solar activity is demonstrated. The number of aviation accidents for year 2010 is forecasted